2016
DOI: 10.1007/s13205-016-0540-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of used engine oil by novel strains of Ochrobactrum anthropi HM-1 and Citrobacter freundii HM-2 isolated from oil-contaminated soil

Abstract: Used engine oil (UEO) constitutes a serious environmental problem due to the difficulty of disposal off or reuse. Ten bacterial strains with biodegradation potential were isolated from UEO-contaminated soil sample using enrichment technique. Two strains which exhibited the highest degradation %, 51 ± 1.2 and 48 ± 1.5, respectively, were selected. Based on the morphological, biochemical characteristics and 16S rRNA sequence analysis, they were identified as Ochrobactrum anthropi HM-1 (accession no: KR360745) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 31 publications
2
38
0
2
Order By: Relevance
“…Heavy metal tolerance test during biodegradation of crude oil investigated by Tiku et al [8] showed that some crude oil degraders were tolerant to cadmium at concentrations of 20, 100, 200, 250, and 300 µg/ml. The presence of lead and cadmium in the concentration ranges of 0.21-0.15 mg/kg and 2.10-1.2 mg/kg respectively were also reported by Ibrahim [34] in the biodegradation of used engine oil by novel strains of Ochrobactrum anthropi HM-1 and Citrobacter freundii HM-2.…”
Section: Percentage Biodegradation Of Diesel Oil During the Biodegradsupporting
confidence: 68%
“…Heavy metal tolerance test during biodegradation of crude oil investigated by Tiku et al [8] showed that some crude oil degraders were tolerant to cadmium at concentrations of 20, 100, 200, 250, and 300 µg/ml. The presence of lead and cadmium in the concentration ranges of 0.21-0.15 mg/kg and 2.10-1.2 mg/kg respectively were also reported by Ibrahim [34] in the biodegradation of used engine oil by novel strains of Ochrobactrum anthropi HM-1 and Citrobacter freundii HM-2.…”
Section: Percentage Biodegradation Of Diesel Oil During the Biodegradsupporting
confidence: 68%
“…All of the strains were capable of using diesel oil as the sole carbon source. Compared with previous investigations , for example, Hong reported that there were nine strains isolated from the oil‐contaminated soil in Korea; and Ibrahim reported that ten strains were isolated from oil‐contaminated soil; Saadoun reported that there were five strains isolated from the soil samples that had been exposed to the crude petroleum oil spills; Kumar reported that there were four fluoranthene degrading strains isolated from the petroleum sludge. In addition, there were 12 strians isolated on this study, so the isolation efficency is relatively higher.…”
Section: Discussionmentioning
confidence: 68%
“…Olawale, et al [8] state that bioremediation has many advantages for detoxification of toxic substances because it is an environmentally friendly and simple method. Bioremediation depends on the ability of microorganisms to degrade diesel pollutants [9]. Some bacteria isolated from diesel contaminated areas have the ability to produce enzymes for degrading and utilizing diesel as carbon and energy source [10].…”
Section: Introductionmentioning
confidence: 99%